System Early Warning Sebagai Peringatan Dini Untuk Smart Home - Ali Nurdin; Lindawati Lindawati; Aden Jaya Kusuma (Forum Kerjasama Pendidikan Tinggi (FKPT), 2020)
Floods, fires and gas leaks that occur often cause problems that can result in losses that are not small in value. The absence of an early warning system when floods, fires and gas leaks make people less alert. In this study designed a flood detection system, fire detection and leak detection in gases that work automatically based on a microcontroller. The water level monitoring system is carried out by using an HC-SR04 type ultrasonic sensor that will read the water level, the fire monitoring system is carried out by using a DHT11 type temperature sensor that will detect the occurrence of fire while the gas leak monitoring system is carried out by using a gas sensor type MQ-9 will find out the gas leak. If all three sensors detect parameters such as rising water levels, rising temperatures and high gas concentrations, the system will sound the buzzer as an early warning sign. This system connected to the Internet of Things (IoT) which will display data in real time displayed using the web-based IoT Platform, Mapid. With this system, it is expected that the public can be more alert to floods, fires and gas leaks.